2010
DOI: 10.12693/aphyspola.117.166
|View full text |Cite
|
Sign up to set email alerts
|

NMR Analysis of Mg Ion Localization in LiNbO3Crystal

Abstract: The analysis of cation sublattices population in magnesium doped LiNbO 3 crystals is carried out. It is shown that volume concentration of lithium vacancies (V Li ) monotonously increases with increasing of MgO content in the crystal up to the threshold value. A series of LiNbO 3 crystals with various concentration of Mg 2+ were investigated by 7 Li and 93 Nb Nuclear Magnetic Resonance (NMR). It is concluded that the peculiarities of NMR spectra in Mg-doped LiNbO 3 crystals can be explained by the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…For higher concentrations, the Mg 2þ ions substitute simultaneously 2/3 of the Li sites and 1/3 of the Nb sites. NMR measurements performed the same year by Yatsenko et al 7 have confirmed that Mg can occupy both Li and Nb sites. Recently, this group of researchers concluded that the most probable kind of structures in magnesiumdoped lithium niobate (MgLN) are defect complexes (4Mg • Li þ 4V 0 Li ).…”
Section: Introductionmentioning
confidence: 77%
“…For higher concentrations, the Mg 2þ ions substitute simultaneously 2/3 of the Li sites and 1/3 of the Nb sites. NMR measurements performed the same year by Yatsenko et al 7 have confirmed that Mg can occupy both Li and Nb sites. Recently, this group of researchers concluded that the most probable kind of structures in magnesiumdoped lithium niobate (MgLN) are defect complexes (4Mg • Li þ 4V 0 Li ).…”
Section: Introductionmentioning
confidence: 77%
“…A series of LiNbO 3 crystals with various concentration of Mg 2 þ were investigated by 93 Nb and 7 Li NMR spectroscopies and it was concluded that the peculiarities of NMR spectra in Mg-doped LiNbO 3 crystals are explained by the formation of defect complexes including MgLi ions and VLi on the shortest distances between them. 109 For four-and six-coordinate niobate systems, the 93 Nb NMR interaction parameters such as the isotropic chemical shift (d iso ), quadrupole coupling constant and asymmetry parameter (C q and Z q ), chemical shift span/anisotropy and skew/asymmetry (O/Dd and k/Zd) and Euler angles (a, b, g) describing the relative orientation of the quadrupolar and chemical shift tensorial frames were discussed. 110 The measurements by variable B 0 approach coupled with the VOCS (variable offset cumulative spectroscopy) technique revealed that the 93 Nb electric field gradient tensor is a particularly sensitive measure of the immediate and extended environments of the NbV positions, with C q values and the d iso and O values are also sensitive to structural disposition.…”
Section: Barium ( 137 Ba) (I = 3/2) the Local Ba Environment In B-bamentioning
confidence: 99%
“…Silver(I) complex [Ag(diene) 2 ] þ Y À (where diene = cyclooctadiene, norbornadiene and 1,3-cyclohexadiene; Y À = PF 6 À , BF 4-) efficiently catalyses the arylation of N-tosylaziridines with arenes and heteroarenes under ambient conditions to provide the corresponding b-aryl amine derivatives with excellent regioselectivity. The following studies were conducted with the help of in situ NMR ( 1 H, 31 P, 109 Ag) and ESI-MS probe: (I) evaluation of Hammett reaction constant (r); (II) correlation of initial rate (k) vs. cone angle (y) of ligand L for reactions mediated by [Ag(COD) 2 ]PF 6 /L (where L is a phosphine or a phosphite ligand); (III) identification of silver-arene intermediates in solution; and (IV) correlation of initial rate (k) with DHOMO-LUMO of [Ag(diene) 2 ]PF 6 obtained from preliminary DFT studies. 148 High-resolution solid-state 109 Ag and 31 P NMR spectroscopy was used to study Ag dialkylphosphite salts, Ag(O)P(OR) 2 (R = CH 3 , C 2 H 5 , Bu and C 8 H 17 ), and determined whether they adopt keto, enol or dimer structures in the solid state.…”
Section: Barium ( 137 Ba) (I = 3/2) the Local Ba Environment In B-bamentioning
confidence: 99%
See 2 more Smart Citations